PETANDA PERADANGAN hs CRP DENGAN HIPERTENSI - Suswanto .; Siti Muchayat P (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
The major pathophysiologic mechanisms of hypertension include the activation of sympathetic nervous system and rennin–angiotensin–aldosterone system. Endothelial dysfunction, increased vascular reactivity, and vascular remodeling may cause that matter,rather than its consequences, of blood pressure elevation; increased vascular stiffness, which contributes to isolate systolic hypertensionin the elderly persons. Chronic low grade inflammation has been identified as an integral part in the pathogenesis of vascular disease.Inflammation may also be implicated in the development of hypertension. Several studies have demonstrated a significant relationshipbetween hs-CRP and stiffness of large arteries. If inflammation is truly linked to hypertension, then it would be reasonable to assume thatdrugs with anti-inflammatory actions may be able to arrest inflammation, improve endothelial function and lowering blood pressurein patients with hypertension. The aim of this cross sectional design study is to observe high sensitive C-reactive protein (hs-CRP)inflammatory markers in thirty five patients with hypertension. also want to know the present correlation between marker inflammationhs CRP with hypertension. With examine to some confounding factors as LDL, GDR and WBC. The results of this study showed that thereis no correlation between hs-CRP and hypertension, especially the duration of hypertension (r = 0.5 and p = 0.002). High degree ofhypertension was not followed by the increasing level of hs CRP.